On the issue of formation of the institutional environment of environmentally safe agricultural land use - Kupriyanchyk, I. (Land Management, Cadastre and Land Monitoring, 2021)
The article is devoted to the formation of the institutional environment of ecologically safe agricultural land use through the model of harmonization of ecological and economic interests of the subjects of agricultural land use. The structure of agricultural land use is based on criteria, the content of which represents both economic and environmental interests of society. For example, the landowner (land user) is interested in converting his land into the most economically attractive - arable land, which reflects his private economic interests, and on the other - society is interested in maintaining the optimal state of agricultural landscapes, which in turn provides the optimal ratio of destabilizing, stabilizing and stabilizing reflecting the public environmental interests [7]. Usually such differentiation of interests of subjects of agrarian land use causes situations of impossibility to agree them voluntarily. Therefore, there is an urgent problem in effective regulatory policy in the field of land use, in particular through the formation of the institutional environment of environmentally friendly agricultural land use through the model of harmonization of environmental and economic interests of agricultural land users. In the article, it is clarified that the institutional model of harmonization of ecological and economic interests of subjects of agrarian land use provides for the introduction of tools to eliminate the conflict of ecological and economic interests, which includes a number of tools, levers and techniques, in particular: -adaptation paradigm; formation of ecological consciousness of land users, ecological morality and ethics; development of the organizational and economic mechanism of formation of ecologically safe agrarian land tenures and land uses optimum through a combination of market and state levers of influence; regulatory and legal support of ecological safety of agricultural land use; optimization of the organizational structure of land use management. Keywords. Institutional environment, institutions, ecologically safe agricultural land use, land relations, economic development, ecology.